Implementasi Good Corporate Governace Guna Meminimalisir Kecurangan Dalam Bank Syariah - Lailatul Hasanah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2020)
In the digital era, what is happening right now does not rule out the possibility in the current banking world that fraud will occur. But even though fraud often causes losses even though in fact in banking in the digital age, we cannot blame the system, a mistake that often occurs repeatedly from the mistakes of human resources who have committed fraud. This happens because humans have a tendency to prioritize themselves as also discussed in agency theory. In addition, objectivity can disappear or diminish when conflicts of interest, emotional ties or other psychological biases occur. Company managers who prepare financial statements can take advantage of the existence of information asymmetry, including having a major influence to determine favorable accounting policies. If sound business ethics is something that companies want to achieve, then applying a principle of Good Corporate Governance can be one of the tools to achieve good business ethics. Implementation using the Good Corporate Governace method puts ethics ahead of the interests of the owner, which is not easy. With the results found that by using and implementing good corporate governance, the data shows that preventing an act of fraud (fraud) that caused a bank or company suffered a large loss.